2018
DOI: 10.1111/ceo.13166
|View full text |Cite
|
Sign up to set email alerts
|

The rising tide of Acanthamoeba keratitis in Auckland, New Zealand: a 7‐year review of presentation, diagnosis and outcomes (2009–2016)

Abstract: AK is a rare vision-threatening protozoal infection with rapidly-increasing incidence in New Zealand, predominantly affecting CL users. Diagnosis is often challenging and when delayed is associated with worse outcomes. IVCM offers rapid diagnosis with high sensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
2
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 45 publications
1
32
2
3
Order By: Relevance
“…It is widely known that contact lens wear is the main risk factor for the development of AK in developed countries. The percentage of patients wearing contact lenses in our series was 95, comparable to 93.5–96% and 96–100% in recent studies from the United Kingdom and New Zealand [11,14]. Soft contact lens wearers were slightly overrepresented in our study population: 74% versus 67% of the contact lens wearers in the general Dutch population [15].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…It is widely known that contact lens wear is the main risk factor for the development of AK in developed countries. The percentage of patients wearing contact lenses in our series was 95, comparable to 93.5–96% and 96–100% in recent studies from the United Kingdom and New Zealand [11,14]. Soft contact lens wearers were slightly overrepresented in our study population: 74% versus 67% of the contact lens wearers in the general Dutch population [15].…”
Section: Discussionsupporting
confidence: 82%
“…Most cases occurred in summer and autumn, as is shown in Fig 2. A high AK incidence in summer and autumn was also found in studies from Canada and New Zealand [10,11]. An American study reported high incidences in June and November, which correlated to the number of amoebae found in surface water [12].…”
Section: Discussionmentioning
confidence: 64%
“…AK is an emerging disease with an increasing number of cases presenting each year worldwide, mostly due to the increasing use of contact lens 2. Several papers showed that the incidence of AK was recently increasing in UK, India, and New Zealand 35. Additionally, recent AK cases (2013–2015) were reported to be more severe than previous (2009–2012) cases 6.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, some cultures may take days to weeks to become positive. For example, a recent study showed positive microscopy or culture results for acanthamoeba in 27.1% of laboratory samples, with positive results reported at a mean of 9.4 days . The diagnostic sensitivity of corneal scrape culture in acanthamoeba keratitis is also low (33% [95% CI, 9.9%‐65.1%]) …”
Section: Diagnosing Infective Keratitismentioning
confidence: 99%